Coagulation factor XIII deficiency - Biswas, A.; Ivaskevicius, V.; Thomas, A.; Oldenburg, J. (Hämostaseologie, 2014)
The plasma circulating zymogenic coagulation factor XIII (FXIII) is a protransglutaminase, which upon activation by thrombin and calcium cross-links preformed fibrin clots/fibrinolytic inhibitors making them mechanically stable and less susceptible to fibrinolysis. The zymogenic plasma FXIII molecule is a heterotetramer composed of two catalytic FXIII-A and two protective FXIII-B subunits. Factor XIII deficiency resulting from inherited or acquired causes can result in pathological bleeding episodes. A diverse spectrum of mutations have been reported in the F13A1 and F13B genes which cause inherited severe FXIII deficiency. The inherited severe FXIII deficiency, which is a rare coagulation disorder with a prevalence of 1 in 4 million has been the prime focus of clinical and genetic investigations owing to the severity of the bleeding phenotype associated with it. Recently however, with a growing understanding into the pleiotropic roles of FXIII, the fairly frequent milder form of FXIII deficiency caused by heterozygous mutations has become one of the subjects of investigative research. The acquired form of FXIII deficiency is usually caused by generation of autoantibodies or hyperconsumption in other disease states such as disseminated intravascular coagulation. Here, we update the knowledge about the pathophysiology of factor XIII deficiency and its therapeutic options.
Keywords: Factor XIII; transglutaminase; heterozygous deficiency; heterotetramer